2009
DOI: 10.1016/j.jjcc.2008.11.005
|View full text |Cite
|
Sign up to set email alerts
|

Waon therapy improves the prognosis of patients with chronic heart failure

Abstract: Waon therapy reduced cardiac events in patients with CHF. This therapy is a promising non-pharmacological treatment for CHF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
65
0
6

Year Published

2010
2010
2018
2018

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 68 publications
(72 citation statements)
references
References 14 publications
0
65
0
6
Order By: Relevance
“…Waon therapy significantly decreased the rate of death or hospitalization in patients with CHF in comparison with the non-Waon therapy group (Figure 2). 8 This retrospective follow-up study demonstrated that Waon therapy reduced cardiac events related to heart failure over a 60-month period. We therefore recommend that Waon therapy should be continued at least twice weekly after discharge in order to maintain its effect on CHF.…”
Section: Effect Of Waon Therapy On Chfmentioning
confidence: 84%
“…Waon therapy significantly decreased the rate of death or hospitalization in patients with CHF in comparison with the non-Waon therapy group (Figure 2). 8 This retrospective follow-up study demonstrated that Waon therapy reduced cardiac events related to heart failure over a 60-month period. We therefore recommend that Waon therapy should be continued at least twice weekly after discharge in order to maintain its effect on CHF.…”
Section: Effect Of Waon Therapy On Chfmentioning
confidence: 84%
“…Furthermore, it is also anticipated that Waon therapyinduced neurohumoral modulation may reverse cardiac remodeling, leading to improved adverse outcomes in those specific HF subtypes, as shown by a retrospective study that Waon therapy reduced cardiac death and rehospitalization in chronic HF patients. 15 Given the pivotal role of Waon therapy in the optimization of systemic neurohumoral factors, the subanalysis study provides a novel insight into the pathophysiological mechanism of Waon therapy for chronic HF. 11 However, it should be noted that the follow-up period of the current study was relatively short, and thus the long-term effect of Waon therapy on cardiac function and prognosis of HF remains to be determined.…”
Section: Article P 709mentioning
confidence: 99%
“…[1][2][3] The precise mechanisms of the salutary effects of WT in CHF treatment are not yet fully understood, although WT-induced vasodilation and improvement of endothelial function through up-regulation of endothelial nitric oxide synthase (eNOS) could contribute to the beneficial effects. 4,5) Depressive symptoms are common in patients with CHF and many CHF patients have impairment of all aspects of their quality of life (QOL) as assessed by SF-36 scores.…”
mentioning
confidence: 99%